2010
DOI: 10.1177/1362361309346558
|View full text |Cite
|
Sign up to set email alerts
|

How Parents Perceive and Feel about Participation in Community Activities

Abstract: The present study compared how parents of preschoolers with and without Autism Spectrum Disorders (ASD) perceived and felt about participation in community activities. A questionnaire survey was conducted with 380 Hong Kong parents of preschoolers with ASD and 214 Hong Kong parents of preschoolers without ASD. The two groups were not different in their willingness and frequency of participation in community activities. However, the psychological processes underneath their willingness were very different. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
(25 reference statements)
0
32
1
Order By: Relevance
“…The results indicate an insignificant relationship between the parents' affiliate stigma and the frequency of their children's participation, which does not fully match our hypotheses that affiliate stigma might lead to reduced participation in community activities. Our findings, however, may be reflected in a study by Lam et al [23], in which the parents of preschoolers with ASD showed high levels of negative emotion and low willingness to take their children out, and these two variables were found to have no association with the participation frequency in community activities. One reason for the similarity in findings between our study and that of Lam et al could be that participation in some community activities is habitual (or obligatory) for the children and families.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The results indicate an insignificant relationship between the parents' affiliate stigma and the frequency of their children's participation, which does not fully match our hypotheses that affiliate stigma might lead to reduced participation in community activities. Our findings, however, may be reflected in a study by Lam et al [23], in which the parents of preschoolers with ASD showed high levels of negative emotion and low willingness to take their children out, and these two variables were found to have no association with the participation frequency in community activities. One reason for the similarity in findings between our study and that of Lam et al could be that participation in some community activities is habitual (or obligatory) for the children and families.…”
Section: Discussioncontrasting
confidence: 80%
“…In fact, for preschool-aged children with ASD, the family plays a crucial role in determining the type and number of activities in which the children will be given opportunities for participation [22]. For example, Lam and her colleagues [23] found that parents' willingness to take their child with ASD to engage in community activities was associated with the degree of difficulty and negative emotions of the children as perceived by the parents. However, this association was not observed in children with typical development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preschoolers with ASD have been found to participate less frequently in self-care, community mobility, vigorous leisure, and sedentary leisure than do children with typical development (LeVesser & Berg, 2011). Caregivers of preschool children with ASD report less frequent and less diverse activity participation (Lam, Wong, Leung, Ho, & Au-Yeung, 2010). Special event activities, such as birthday parties and family vacations, have also been reported as less frequent among preschool and school-age children with ASD (Rodger & Umaibalan, 2011).…”
Section: Literature Reviewmentioning
confidence: 96%
“…The presence of emotional strain and relationship difficulties likely make it more difficult for children with ASD to learn appropriate social behaviors, as more maladaptive interactions are modeled by caregivers who are frequently engaged in conflict. An increase in family conflict may also create a barrier to participating in enjoyable and potentially beneficial activities, as families of children with ASD have been found to limit involvement in community activities (Lam et al 2010). Notably, Kelly et al (2008) noted that family conflict was predictive of ASD symptom presentation and found that negative family relationships influenced ASD symptom manifestation more than positive family interactions.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%